Keratometric changes after cataract extraction. Issue 9 (September 1976) - Singh, D; Kumar, K
Abstract : One hundred cases of uncomplicated cataract with clear corneae had cataract extraction and were examined at 20 days and six weeks after operation. Keratometry was done preoperatively and keratometry and retinoscopy at each of the follow-up visits. The study was undertaken to evaluate the type (whether pre- or postplaced) and the number of sutures (one, three, or five) that produce the least postoperative astigmatism. We found that the type of suture was immaterial but that three sutures produced the least astigmatism.